2019
DOI: 10.1186/s12870-019-1869-9
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Threonine-1050 of SlBRI1 regulates BR Signalling and increases fruit yield of tomato

Abstract: Background Appropriate brassinosteroid (BR) signal strength caused by exogenous application or endogenous regulation of BR-related genes can increase crop yield. However, precise control of BR signals is difficult and can cause unstable effects and failure to reach full potential. Phosphorylated BRASSINOSTEROID INSENSITIVE1 (BRI1), the rate-limiting receptor in BR signalling, transduces BR signals, and we recently demonstrated that modifying BRI1 phosphorylation sites alters BR signal strength and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The supernatants (100 μL) were subjected to ELISA according to the manufacturer’s instructions (MyBioSource). Optical density was measured at 450 nm using a microplate reader (Molecular Devices, Sunnyvale, CA, USA), as described previously [71].…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants (100 μL) were subjected to ELISA according to the manufacturer’s instructions (MyBioSource). Optical density was measured at 450 nm using a microplate reader (Molecular Devices, Sunnyvale, CA, USA), as described previously [71].…”
Section: Methodsmentioning
confidence: 99%
“…Several bri1 -defective mutants of many species exhibit a semi-dwarf phenotype and decreased stem-leaf angles, which are recognized as indispensable attributes for intensive agriculture [ 15 , 19 , 48 ]. We previously reported that SlBRI1-overexpressing plants exhibited increased tomato yields, and dephosphorylated Thr-1050 of SlBRI1 could promote tomato yield by compacting plant architecture, as well as increasing fruit number and fruit weight, under normal conditions [ 16 , 25 ]. In the present investigation, the effects of Ser-1040 of SlBRI1 on tomato yield were distinct from those of Thr-1050.…”
Section: Discussionmentioning
confidence: 99%
“…Dephosphorylation of Thr-1054 in SlBRI1 severely attenuated BR signalling and disturbed plant growth in tomato [ 24 ]. Our previous study further found that the tomato SlBRI1 phosphorylation site Thr-1050 could affect tomato yield by regulating BR signalling [ 25 ]. These results suggest the potential value of phosphorylation sites of BRI1 in crop agronomic trait improvement, given their precise modification of the biological function of BRI1.…”
Section: Introductionmentioning
confidence: 99%
“…In tomato, the BR biosynthetic gene DWF affects fruit yield by regulating architecture, and the BR level was found to be positively correlated with carotenoid accumulation in the fruits (Li et al, 2016). BR was found to promote tomato yield through enhanced autophosphorylation of SlBRI1, and increased plant expansion, leaf area, fruit weight, and number of fruits per cluster (Wang et al, 2019). Brassinolide (BL), 28homobrassinolide (28-hBL), and 24-epibrassinolide (24-eBL) treatments stimulated both the growth and yield of tomato plants (Vardhini and Rao, 2001).…”
Section: Regulation Of Yield By Brassinosteroid In Different Cropsmentioning
confidence: 99%